Metazoan parasite fauna of two peacock-bass cichlid fish in Brazil - Yamada, Fabio Hideki [UNESP]; Takemoto, Ricardo Massato (Pensoft Publishers, 2013)
A parasitological study of two freshwater cichlid fish of the genus Cichla (C. kelberi and C. piquiti) from six different aquatic ecosystems in Brazil was performed. Based on the survey, a checklist of the component community of the metazoan parasites of each of the two peacock-bass fish species was produced. Fish were collected from May 2009 to April 2011 in six Brazilian aquatic ecosystems using gillnets of different mesh sizes or angling using standardized effort. In total, six groups of parasites were collected: Monogenea, Digenea, Cestoda, Nematoda, Copepoda and Branchiura. Among the groups of parasites found, nematodes presented the greatest number of species, with seven. The study lists new records of parasites in C. kelberi and C. piquiti, and new biogeography records of parasites in six different aquatic ecosystems in Brazil. The present paper collaborates with the study of conservation biology by adding new records of parasite species. © 2013 Check List and Authors.